Three-year pooled analysis of factors associated with clinical outcomes across dabrafenib and trametinib combination therapy phase 3 randomised trials. (September 2017) - Schadendorf, Dirk; Long, Georgina V.; Stroiakovski, Daniil; Karaszewska, Boguslawa; Hauschild, Axel; Levchenko, Evgeny; Chiarion-Sileni, Vanna; Schachter, Jacob; Garbe, Claus; Dutriaux, Caroline; Gogas, Helen; Mandalà, Mario; et al.
Abstract: Aim: Understanding predictors of long-term benefit with currently available melanoma therapies is the key for optimising individualised treatments. A prior pooled analysis of dabrafenib plus trametinib (D + T)–randomised trials (median follow-up, 20.0 months) identified baseline lactate dehydrogenase (LDH) and number of organ sites with metastasis as predictive factors for progression-free (PFS) and overall (OS) survival. However, longer-term follow-up analyses are needed to confirm which patients treated with D + T can achieve maximum benefit. Methods: Three-year landmark data were retrospectively pooled for D + T patients in phase 3 trials (COMBI-d [NCT01584648]; COMBI-v [NCT01597908]). Univariate and multivariate analyses assessed prognostic values of predefined baseline factors; regression tree analysis determined hierarchy and interactions between variables. Results: Long-term pooled outcomes were consistent with individual trial results (N = 563; 3-year PFS, 23%; 3-year OS, 44%). Baseline LDH level and number of organ sites remained strongly associated with and/or predictive of PFS and OS. In addition, baseline sum of lesion diameters (SLD) was identified as a predictor for progression. In the most favourable prognostic group (normal LDH, SLD <66 mm, <3 organ sites; n = 183/563 [33%]), 3-year PFS was 42%. Baseline number of organ sites was also predictive of outcomes in patients with PFS ≥ 6 months. Conclusion: Using the largest phase 3 data set available for BRAF/MEK inhibitor combination therapy in melanoma, these results demonstrate that durable responses lasting ≥3 years are possible in subsets of patients with BRAF -mutant melanoma receiving D + T. Although the best predictive model evolved with longer follow-up, factors predicting clinical outcomes with the combination remained consistent with previous analyses. Highlights: Efficacy data remained consistent across phase 3 dabrafenib plus trametinib trials. Baseline lactate dehydrogenase level and number of organ sites with metastasis remained predictive of progression-free survival and overall survival. Baseline sum of lesion diameters was also identified as a predictor for progression-free survival with extended follow-up. Durable responses with targeted therapy are possible in BRAF -mutant melanoma.